Presenting a structural model of analyzing the relationship between family communication patterns and achievement motivation with emphasis on the mediating role of students' academic adjustment - Leila Talebi Khansari (Institute of Management fekrenoandish, 2021)
Extended AbstractAbstractThe aim of this study was to present a structural model of analyzing the relationship between family communication patterns and achievement motivation with emphasis on the mediating role of academic adjustment of Qazvin junior high school girls. The research method is essentially descriptive-correlative. The statistical population of the study consists of 2613 students of Qazvin high school girls. The sample size was obtained by cluster random sampling of 270 people. Data were collected using the Ritchie and Fitzpatrick (1990) Communication Patterns Questionnaire, Hermans' Progress Motivation Questionnaire (1970), and Sinha and Singh (1993) Academic Adjustment Questionnaire, which was validated by academic experts and its reliability also confirmed by Cronbach's alpha coefficient test. In order to analyze the data, the structural equation technique was used by means of Lisrel statistical software and Spss statistical software. Findings showed that family communication patterns had a direct and indirect relationship with students' achievement motivation and academic adjustment played a mediating role in this relationship.IntroductionThe success and efficiency of educational systems depends on the academic achievement of students in the courses (Talebi Khansari, 2020). The progress and decline of students' academic courses is a touchstone for the efficiency of the educational system and the discovery and study of effective variables on these variables lead to a better understanding and prediction of effective factors in school. Therefore, the study of variables related to academic achievement in different courses is one of the main topics of research in the education system (Aboutalebi, 2021). Academic success and achievement in any society indicates the success of the educational system in the field of targeting and paying attention to meeting individual needs; therefore, the educational system can be defined Effective and successful when the academic achievement of its students in different courses comes up to the highest figure (Mirarab, Azizi Shomami, & Grayli, 2019). Academic achievement and success are related to factors such as motivation and cognitive processing (Tavakoli, Hasanzadeh, & Emadian, 2020). Progress motivation reflects the tendencies to effort for achieve success and the positive effects associate with that, and avoidance of failure and its negative effects (Arakeri, Sunagar, 2017). People who are motivated to progress succeed in tasks that have a higher degree of difficulty, and work hard to achieve success (Narasimhan, 2018). Lack of motivation to do a task can make it difficult to achieve results (Shekhar, Kumar, 2016). Communication skills seem to be one of the factors influencing students' academic achievement motivation; as Harrison et al. (2007) believe, a good and successful teacher-student relationship improve and increase academic adjustment. Each student in the process of their social development, to progress and flourish their talents and desired adaptability with the environment and those around them requires the acquisition of communication skills that begin in the process of socialization with the family and are shaped by the growth and age of individuals in the school and community (Petrovici, Dobrescu, 2014). Interpersonal communication occurs when people interact with each other. Every relationship is an exchange in which at least two people must participate, and during the interaction of people with each other, a social lifestyle is formed (Dehestsni, Ebrahimi, Aboohashemi Moghaddam, 2020). Another important dimension in academic achievement is academic adaptation (Sharifi rigi, 2018). Academic adaptation refers to the ability of learners to adapt to the conditions and requirements of education and the plans set by the school and the university as a social institution (Tamanei far, Moradi, 2015). Admission to university and transfer from high school to university is a big and major change in the lives of many young people. Going to university is an opportunity to learn more about mental development (Faridland., Ridd., Shapak., Keribi, 2007). But at the same time, it is a source of stress for some people and causes inconsistent reactions in them. Therefore, considering the above and considering the role of academic adjustment and the type of relationship between students and family in motivation for academic achievement and success in future life, the present study seeks to answer the question that what the appropriate structural model in relation to family communication patterns and achievement motivation by emphasizing the mediating role of academic adjustment of high school girls is.Theoretical frameworkHarrison et al. (2007) believe that a good and successful relationship between teacher and student improves and increases academic adjustment. Each student in the process of social development, in order to develop and flourish their talents and adapt to the environment and entourage, need to acquire communication skills that in the process of socialization, begins with the family. Shudrichi (1991) named the following items; conceptual orientation because of the importance of expressing ideas, dialogue orientation and social orientation because of following others to conformity orientation.Aboutalebi (2021) in an article examined the effect of academic enthusiasm and academic seriousness on the academic achievement of female elementary school students in the 7th district of Karaj and came to the conclusion that academic seriousness leads to academic self-fulfillment (Aboutalebi, 2021).. Kordloo and Behrangi (2020) in a study entitled "The size of the effect of the intellectual scaffolding of education management In the application of new educational technologies on academic motivation and achievement in science course in fifth grade elementary school female students" conducted on 297 fifth grade female elementary school students in districts 1 and 2 of Tehran, showed that the teaching model of education management based on rational scaffolding is effective in increasing motivation and academic achievement of science courses (Kordloo, Behrangi, 2020). Talebi Khansari (2020) in a study examined the relationship between classroom management practices and communication skills with the academic achievement motivation of elementary school students in Chabaksar and concluded that teachers can use effective classroom management styles and communication skills to increase students' motivation for academic achievement and prevent burnout and academic failure (Talebi Khansari, 2020).MethodologyThe present study is a methodological description of correlation. The statistical population of this study consisted of 2613 students of girls' secondary schools in Qazvin. Due to the large size of the statistical population, three schools were randomly selected and one class was selected from each school, which includes the seventh, eighth and ninth grade. A total of 9 classrooms were selected with a student population of 270. The sampling method was cluster random. Ritchie and Fitzpatrick (1990) communication patterns questionnaire was used for collecting data related to students' communication patterns variable, Sinha and Singh (1993) academic adjustment questionnaire for academic adjustment variable, Hermans Progress Motivation questionnaire (1970) for progress motivation variable.Discussion and ResultsTo model the final structural equations, the mediating role of academic adjustment in the relationship between family communication patterns and achievement motivation in students has been used. In order to investigate the mediating effect of academic adjustment in the hypothesis under discussion, the direct effect of the two structures with the indirect effect in the case of involving the mediating variable should be considered so that if the effect increases, the mediating effect can be considered acceptable. In the present hypothesis, the effect is equal to 0.59.